Karakter Fisiologi dan Pendugaan Heritabilitas Tanaman M1 Bawang Merah (Allium Ascalonicum L.) Hasil Induksi Iradiasi Sinar Gamma - Lika Alfariatna; Florentina Kusmiyati; Syaiful Anwar (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
ABSTRACTThe aim of the research was to determine the physiological characters, heritability estimation, and information of lethal doses (LD50) of M1 onion plant induced by gamma ray irradiation. The research was arranged in monofactor experimental with Complete Randomized Design (CRD) with 6 treatments and 5 replication, each replication consisted of 5 onion bulbs was irradiated by gamma ray of 0, 3, 6, 9, 12, 15 Gy. Parameters observed: the percentage of germination, chlorophyl content, nitrate reductase activity, heritability estimation and LD50. The data were analyzed by anova and followed by BNT 5% level. The result showed that irradiation significant affected to chlorophyl content and nitrate reductase activity. LD50 of onion is 7,64 Gy. Heritability value range from 52,22 – 80,51%. Keywords : Allium ascalonicum L.,irradiation, LD50, heritability